BIOKONTROL ENDOMIKORIZA TERHADAP JAMUR Curvularia sp. PENYEBAB PENYAKIT TANAMAN JAGUNG (Zea mays L.) - Windasari, Lily; Proborini, Meitini Wahyuni; Ria Defiani, Made (SIMBIOSIS, 2019)
In Indonesia, production of corn are used for fodder (55%), food (30%), and seed (15%). The growth of corn plants is limited by the presence of pests, weeds, and plant diseases. Curvularia sp. causing leaf spot and could decrease corn production. Use of mycorrhiza can be used as a biological agent in preventing pathogens outbreaks. Isolates of Curvularia sp. fungal was sprayed on corn seed. This research was conducted in laboratorium and green house. Corn seedlings were grown on sterile soil media (control), mycorrhizal treatments (100g of mycorrhizal + Curvularia sp., 200g of mycorrhizal + Curvularia sp., 300g of mycorrhizal + Curvularia sp.) and Curvularia sp. The observed variables were plant height, number of leaves, rate of disease progression, fresh weight and dry weight of plant canopy. The results showed that application of 100g inoculum tend to increase plant growth to 26-27% and percentage of mycorrhizal colonization to 58,66% thereof can decrease pathogen infection on plant at 28 day after planting.